Menentukan Pengendalian dan Persediaan Bahan Baku Pada CV. XYZ dengan Metode EOQ - Alan Akbar Bukhori; Andri Herlambang; Syahputra Amri (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Increased productivity the company, one of the indicators that can be seen is the optimal supply of raw materials for the company. This research examines as well as applies the economic order quantity (EOQ) method in controlling raw materials at CV XYZ which is engaged in the manufacture of stone blocks. From the research results, it was found that the optimal amount of inventory in 2022 was 631,230 kg for sand material with a frequency of 3 times, safety stock was around 116,663 kg, reordering (Re Order Point) reached 145,293 kg and for cement the optimal supply was 137,455 kg with a frequency of 1 time, and for safety stock of 7,521 kg, and to place orders again when the inventory level reaches 9,439 kg, so that the total cost of the two materials is Rp. 77,220,526.